Perencanaan Strategis Sistem Informasi Menggunakan Metode Wetherbe (Studi Kasus : Kantor Sekretariat Majelis Rakyat Papua) - Mardiana Fingkreuw (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Majelis Rakyat Papua is an institution in the province of Papua, Indonesia consisting of indigenous Papuans who are equivalent to the DPRD. As the Papuan People's Assembly develops, it will affect the needs of information technology. Currently to create a peaceful Papua as an embodiment of the commitment of all components of society in the province, the duties and functions of the Papuan People's Assembly, information systems are needed to support organizational activities, services to stakeholders, especially to indigenous Papuans. However, so far the utilization of the information system to support the main task and its function has not been maximized because some of the processes are still done manually, so it is less effective and efficient. Therefore, research on Strategic Planning of Information Technology will be needed to ensure the success of the Papuan People's Assembly in meeting information technology needs using the Wetherbe methodology. Through good and appropriate information technology planning, the purpose of the MRP is that both short-term and long-term can be done optimally. The preparation of a strategic plan of information systems has resulted in a portfolio of information systems applications. Strategic planning of this information system can create a strategy that is aligned with the business strategy of the Sekretariat Majelis Rakyat Papua. The solution needs information systems based on the results of the analysis that has been done, resulting in twenty two information systems.